Perceptions of adults with obesity about multiprofessional remote monitoring at the beginning of the COVID-19 pandemic - Heloá Costa Borim Christinelli; Dandara Novakowski Spigolon; Élen Ferraz Teston; Maria Antonia Ramos Costa; Greice Westphal; Nelson Nardo Junior; Carlos Alexandre Molena Fernandes (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To understand the perception of adults with obesity about remote monitoring at the beginning of the pandemic of COVID-19. Methods: A descriptive-exploratory, qualitative study with participants in remote monitoring of a multi-professional treatment program in southern Brazil. Data was collected through digital platforms with interviews in written or audio-recorded records. The results were submitted to content analysis, thematic modality. Results: 26 women participated, emerging the thematic category "Difficulties and potentialities in adherence to lifestyle changes during the pandemic. Among the difficulties are the change of routine and increased anxiety; and, among the potentialities are the multi-professional accompaniment, decreased tension, and weight control. Final considerations: The participants' perception showed considerable weaknesses in adhering to the program, caused by social distance. Studies with remote interventions are essential to improve the quality of this type of health care.